A rubber compound for improving tire grip performance by changing resin type
By combining polyetheramine resin with high specific surface area porous silica and forming a crosslinking network with rubber and other materials, the problem of existing tire materials sacrificing anti-slip properties when reducing rolling resistance is solved, and better grip performance and high temperature stability are achieved.
Patent Information
- Application Number
- CN202411595239.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Existing tire materials usually sacrifice anti-slip properties when reducing rolling resistance, making it difficult to find a balance between the two, affecting the safety performance of the car.
Polyetheramine resin is used to combine with porous silica with high specific surface area, and a cross-linking network is formed by combining the modified resin with natural rubber and oil-filled styrene-butadiene rubber, which improves the modulus and strength of the tire rubber and enhances the grip performance.
It improves the grip and anti-slip performance of the tire, enhances the self-repairing ability and high temperature stability of the tire materials, and ensures that the tire can be effectively covered and prevents gas leakage after being pierced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tire rubber materials, in particular to a rubber material for improving tire gripping performance by changing resin types. Background Art
[0002] With the rapid development of automobile industry and transportation industry, highway construction, especially the rapid development of expressways, various high-performance tires are urgently needed. Automobile tires are particularly important in the use of automobiles, and automobile tires are related to the safety performance of automobiles.
[0003] A car will generate various driving resistances during driving, 80% of which is air resistance and the remaining 20% is rolling resistance. The impact of tire rolling resistance is affected by many factors such as material properties, tire structure, tire production and manufacturing process and usage conditions. Some of these factors affect each other. It is not very difficult to simply reduce tire rolling resistance, but it usually requires sacrificing certain tire properties, especially wet and slippery resistance. From a safety perspective, tires should maintain a high wet and slippery resistance. Therefore, material selection and tire structure design are important ways to reduce tire rolling resistance. Therefore, a breakthrough must be made in the resin type. Summary of the invention
[0004] The purpose of the present invention is to provide a rubber material for improving the tire grip performance by changing the resin type, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a rubber compound for improving tire grip performance by changing the type of resin, the rubber compound is prepared by the following method:
[0006] (1) Mix polyetheramine, 2,2'-[[2-(allyloxy)-1,3-phenylene]bis(methylene)]bis(ethylene oxide) and catalyst in a molar ratio of 1.5-3:1:0.003, react at 80-135°C for 12-72h under nitrogen protection, and then evacuate to -0.08-0.095MPa for 30-40min to obtain a pretreated resin;
[0007] (2) Take the pretreated resin, ethylene (chloromethyl) dimethoxysilane, sodium ethoxide, and sodium iodide in a mass ratio of 100:1~3:0.1~0.4:0.1~0.4, react at 55~60°C for 12 hours, add water for extraction, take the organic phase, treat it at a vacuum degree of -0.08~-0.095MPa and 60°C for 30~40min, add 0.5~1.0 times the mass of the pretreated resin high specific surface area porous silica, stir at 500~800rpm for 20min, and obtain the modified resin;
[0008] (3) kneading 8-16 parts by weight of modified resin, 30-50 parts by weight of natural rubber, 40-60 parts by weight of oil-extended styrene-butadiene rubber, 30-40 parts by weight of white carbon black, 7-10 parts by weight of silane coupling agent, 1-3 parts by weight of epoxy resin and 4-7 parts of processing oil TDAE at 150° C. for 4 min to obtain rubber A;
[0009] (4) 8-16 parts by weight of modified resin, 30-50 parts by weight of natural rubber, 10-15 parts by weight of carbon black N234, 1-3 parts by weight of silane coupling agent, and 3-6 parts by weight of isocyanate were kneaded at 160° C. for 4 minutes to obtain rubber B;
[0010] (5) Take 100 parts by weight of rubber A and 100 parts by weight of rubber B and mix them at 60 rpm for 5 to 20 seconds. Add 5 to 10 parts by weight of zinc oxide, 1.5 to 2.0 parts by weight of stearic acid, 1 to 3 parts by weight of antioxidant RD, and 3 to 12 parts by weight of antioxidant and mix for 20 seconds. Then add 5 to 8 parts by weight of sulfur and 0.5 to 1 part by weight of vulcanization accelerator NS. After mixing for 3 minutes, drain the rubber at 125°C, leave it at room temperature for 8 hours, and then vulcanize it at 165°C for 30 minutes using a flat vulcanizer.
[0011] Furthermore, the polyetheramine in step (1) is polyetheramine D2000 or polyetheramine M2070.
[0012] Furthermore, the catalyst in step (1) is prepared by mixing boron trifluoride etherate and zinc chloride in a mass ratio of 2:1.
[0013] Furthermore, the high specific surface area porous silica in step (2) is prepared by mixing water glass solution and slaked lime to generate calcium silicate particles, followed by acid leaching, and has a specific surface area of 704-870 m 2 / g.
[0014] Furthermore, the natural rubber in steps (3) and (4) is SMR20.
[0015] Furthermore, the oil-extended styrene-butadiene rubber in step (3) is SBR1712.
[0016] Furthermore, the silane coupling agent in steps (3) and (4) is n-octyltriethoxysilane.
[0017] Furthermore, the epoxy resin in step (3) is one or a mixture of glycidyl ester epoxy resin, glycidyl ether epoxy resin, glycidyl amine epoxy resin, linear aliphatic epoxy resin, and alicyclic epoxy resin.
[0018] Furthermore, the isocyanate in step (4) is isophorone diisocyanate or diphenylmethane diisocyanate.
[0019] Furthermore, the antioxidant in step (5) is a phenylenediamine antioxidant.
[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0021] (1) The present invention uses polyetheramine resin to replace the resin used in traditional tires as one of the main resin raw materials, which can enhance the elasticity of the tire rubber and improve the self-repairing ability of the tire rubber. The amino group of the polyetheramine resin reacts with the diepoxy group of 2,2'-[[2-(allyloxy)-1,3-phenylene]di(methylene)]di(ethylene oxide). The introduction of phenyl groups can be compatible with the rubber in the tire rubber and avoid the incompatibility with the rubber affecting the performance of the rubber. On this basis, the polyetheramine resin reacts with ethylene (chloromethyl)dimethoxysilane to introduce a silane structure into the side chain of the resin, which can then be combined with porous silica to improve the heat resistance of the modified resin and ensure the high temperature stability during the vulcanization process of the tire rubber. The modified resin-silica secondary crosslinking system can indirectly enhance the interaction between rubber and silica and improve the performance of the tire rubber. In addition, the side chain of the modified resin contains multiple unsaturated side groups, which can enhance the grip performance of the tire.
[0022] (2) Porous silica with a larger specific surface area is used instead of traditional silica. The rubber cannot be completely wrapped on its surface, and it can work together with white carbon black to puncture the water film, thereby improving the grip performance of the tire rubber.
[0023] (3) The present invention uses modified resin and natural rubber, oil-extended styrene-butadiene rubber as raw materials, and mixes them with epoxy resin and isocyanate respectively to obtain rubber A and rubber B, and then mixes rubber A and rubber B together to obtain the final rubber. Through the combination of rubber and resin, the strength of the formula can be improved, making the tire more grippy. The epoxy resin and isocyanate can cross-link with the modified resin to introduce a new cross-linking network, thereby improving the modulus and strength of the prepared tire rubber. After the tire is punctured, it can cover the surface of the punctured object to prevent the gas inside the tire from leaking quickly. The mixing process of the present invention can reduce the blending time between different polymers and reduce the blending temperature, thereby reducing the compatibility between multiphase polymers, thereby better maintaining the glass transition temperature characteristics of the polymer itself and maintaining the grip ability. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe the method in detail. The test methods of various indicators of the tire rubber materials prepared in the following examples are as follows:
[0026] Tensile performance test: The rubber materials obtained in the examples and comparative examples were placed in a roller extruder for calendering to obtain samples with a sample size of 100 mm × 10 mm × 3 mm. The tensile properties were tested in accordance with GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber";
[0027] Tire air retention rate: The rubber materials obtained in the examples and comparative examples are made into test tires, mounted on 16-inch test rims, inflated to 250 kPa, and soapy water is used to test whether the tire mouth and valve are leaking. For tires that are confirmed to be airtight, an air pressure gauge is installed on the valve. A 5mm steel nail is used to pierce the tread of the tire, and soapy water is used to test whether the part pierced by the steel nail is leaking. If there is leakage, the test fails. The tire pierced by the steel nail is placed in an environment of 25°C for 24 hours, and the tire pressure is recorded. The ratio of the tire pressure to the inflation pressure after 24 hours is the tire air retention rate.
[0028] Example 1; (1) polyetheramine D2000, 2,2'-[[2-(allyloxy)-1,3-phenylene]di(methylene)]di(ethylene oxide) and a catalyst were mixed in a molar ratio of 2:1:0.003, reacted at 125°C for 24 hours under nitrogen protection, and then evacuated to -0.09 MPa for 30 minutes to obtain a pretreated resin; the catalyst was prepared by mixing boron trifluoride etherate and zinc chloride in a mass ratio of 2:1;
[0029] (2) Pretreated resin, ethylene (chloromethyl) dimethoxysilane, sodium ethoxide, and sodium iodide were mixed in a mass ratio of 100:1:0.2:0.2, reacted at 55°C for 12 hours, and then water was added for extraction. The organic phase was taken and treated at a vacuum degree of -0.08 MPa and 60°C for 35 minutes. A high specific surface area porous silica with a mass of 0.5 times that of the pretreated resin was added, and stirred at 600 rpm for 20 minutes to obtain a modified resin; the high specific surface area porous silica was prepared by mixing water glass solution and slaked lime to generate calcium silicate particles, and then acid leaching, with a specific surface area of 719.2 m 2 / g;
[0030] (3) 8 parts by weight of modified resin, 35 parts by weight of natural rubber SMR20, 55 parts by weight of oil-extended styrene-butadiene rubber SBR1712, 30 parts by weight of white carbon black, 7 parts by weight of n-octyl triethoxysilane, 1 part by weight of linear aliphatic epoxy resin, and 4 parts of processing oil TDAE were kneaded at 150° C. for 4 min to obtain rubber A;
[0031] (4) 8 parts by weight of modified resin, 30 parts by weight of natural rubber SMR20, 10 parts by weight of carbon black N234, 1 part by weight of n-octyltriethoxysilane, and 3 parts by weight of diphenylmethane diisocyanate were kneaded at 160° C. for 4 min to obtain rubber B;
[0032] (5) Take 100 parts by weight of rubber A and 100 parts by weight of rubber B and mix them at 60 rpm for 10 seconds. Add 5 parts by weight of zinc oxide, 1.8 parts by weight of stearic acid, 2 parts by weight of antioxidant RD, and 5 parts by weight of antioxidant and mix them for 20 seconds. Then add 6 parts by weight of sulfur and 0.6 parts by weight of vulcanization accelerator NS. After mixing for 3 minutes, drain the rubber at 125°C, leave it at room temperature for 8 hours, and then vulcanize it at 165°C for 30 minutes using a flat vulcanizer.
[0033] Example 2; (1) polyetheramine D2000, 2,2'-[[2-(allyloxy)-1,3-phenylene]di(methylene)]di(ethylene oxide) and a catalyst were mixed in a molar ratio of 3:1:0.003, reacted at 125°C for 30 hours under nitrogen protection, and then evacuated to -0.095 MPa for 35 minutes to obtain a pretreated resin; the catalyst was prepared by mixing boron trifluoride etherate and zinc chloride in a mass ratio of 2:1;
[0034] (2) Pretreated resin, ethylene (chloromethyl) dimethoxysilane, sodium ethoxide, and sodium iodide were mixed in a mass ratio of 100:2:0.4:0.4, reacted at 60°C for 12 hours, and then water was added for extraction. The organic phase was taken and treated at a vacuum degree of -0.095 MPa and 60°C for 40 minutes. A high specific surface area porous silica with a mass of 0.7 times that of the pretreated resin was added, and stirred at 800 rpm for 20 minutes to obtain a modified resin; the high specific surface area porous silica was prepared by mixing water glass solution and slaked lime to generate calcium silicate particles, and then acid leaching, with a specific surface area of 719.2 m 2 / g;
[0035] (3) 11 parts by weight of modified resin, 45 parts by weight of natural rubber SMR20, 60 parts by weight of oil-extended styrene-butadiene rubber SBR1712, 35 parts by weight of white carbon black, 7 parts by weight of n-octyl triethoxysilane, 2 parts by weight of epoxy resin, and 5 parts of processing oil TDAE were kneaded at 150° C. for 4 min to obtain rubber A; the epoxy resin was prepared by mixing a linear aliphatic epoxy resin and a glycidyl ester epoxy resin in a mass ratio of 1:0.6;
[0036] (4) 10 parts by weight of modified resin, 40 parts by weight of natural rubber SMR20, 12 parts by weight of carbon black N234, 1 part by weight of n-octyltriethoxysilane, and 4 parts by weight of diphenylmethane diisocyanate were kneaded at 160° C. for 4 min to obtain rubber B;
[0037] (5) Take 100 parts by weight of rubber A and 100 parts by weight of rubber B and mix them at 60 rpm for 15 seconds. Add 5 parts by weight of zinc oxide, 1.8 parts by weight of stearic acid, 2 parts by weight of antioxidant RD, and 5 parts by weight of phenylenediamine antioxidant and mix for 20 seconds. Then add 6 parts by weight of sulfur and 0.6 parts by weight of vulcanization accelerator NS. After mixing for 3 minutes, drain the rubber at 125°C, leave it at room temperature for 8 hours, and then vulcanize it at 165°C for 30 minutes using a flat vulcanizer.
[0038] Example 3; (1) polyetheramine M2070, 2,2'-[[2-(allyloxy)-1,3-phenylene]bis(methylene)]bis(ethylene oxide) and a catalyst were mixed in a molar ratio of 2:1:0.003, reacted at 125°C for 24 hours under nitrogen protection, and then evacuated to -0.095 MPa for 40 minutes to obtain a pretreated resin; the catalyst was prepared by mixing boron trifluoride etherate and zinc chloride in a mass ratio of 2:1;
[0039] (2) Pretreated resin, ethylene (chloromethyl) dimethoxysilane, sodium ethoxide, and sodium iodide were mixed in a mass ratio of 100:3:0.4:0.4, reacted at 60°C for 12 hours, and then water was added for extraction. The organic phase was taken and treated at a vacuum degree of -0.095 MPa and 60°C for 40 minutes. A high specific surface area porous silica with a mass 1.0 times that of the pretreated resin was added, and stirred at 800 rpm for 20 minutes to obtain a modified resin; the high specific surface area porous silica was prepared by mixing water glass solution and slaked lime to generate calcium silicate particles, and then acid leaching, with a specific surface area of 719.2 m 2 / g;
[0040] (3) 16 parts by weight of modified resin, 50 parts by weight of natural rubber SMR20, 60 parts by weight of oil-extended styrene-butadiene rubber SBR1712, 40 parts by weight of white carbon black, 10 parts by weight of n-octyl triethoxysilane, 3 parts by weight of linear aliphatic epoxy resin, and 6 parts of processing oil TDAE were kneaded at 150° C. for 4 min to obtain rubber A;
[0041] (4) 16 parts by weight of modified resin, 50 parts by weight of natural rubber SMR20, 15 parts by weight of carbon black N234, 3 parts by weight of n-octyltriethoxysilane and 6 parts by weight of diphenylmethane diisocyanate were kneaded at 160° C. for 4 min to obtain rubber B;
[0042] (5) Take 100 parts by weight of rubber A and 100 parts by weight of rubber B and mix them at 60 rpm for 15 seconds. Add 5 parts by weight of zinc oxide, 1.8 parts by weight of stearic acid, 2 parts by weight of antioxidant RD, and 5 parts by weight of phenylenediamine antioxidant and mix for 20 seconds. Then add 6 parts by weight of sulfur and 0.6 parts by weight of vulcanization accelerator NS. After mixing for 3 minutes, drain the rubber at 125°C, leave it at room temperature for 8 hours, and then vulcanize it at 165°C for 30 minutes using a flat vulcanizer.
[0043] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (2) is changed to: polyetheramine D2000, ethylene (chloromethyl) dimethoxysilane, sodium ethoxide, and sodium iodide are mixed in a mass ratio of 100:2:0.4:0.4, reacted at 60°C for 12 hours, and then water was added for extraction. The organic phase was taken and treated at a vacuum degree of -0.095 MPa and 60°C for 40 minutes. A high specific surface area porous silica with a mass of 0.7 times that of the polyetheramine D2000 was added, and stirred at 800 rpm for 20 minutes to obtain a modified resin; the high specific surface area porous silica was prepared by mixing a water glass solution and slaked lime to generate calcium silicate particles, and then acid leaching, and the specific surface area was 719.2 m 2 / g; the remaining steps are the same as in Example 2.
[0044] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that vinyl (chloromethyl) dimethoxysilane is not added for the reaction, and the remaining steps are the same as Example 2.
[0045] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that ordinary silicon dioxide is used, and the remaining steps are the same as Example 2.
[0046] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that no epoxy resin is added, and the remaining steps are the same as Example 2.
[0047] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that no isocyanate is added, and the remaining steps are the same as Example 2.
[0048] Comparative Example 6; The difference between Comparative Example 6 and Example 2 is that: 11 parts by weight of modified resin, 45 parts by weight of natural rubber SMR20, 60 parts by weight of oil-extended styrene-butadiene rubber SBR1712, 35 parts by weight of white carbon black, 7 parts by weight of n-octyl triethoxysilane, 2 parts by weight of epoxy resin, 5 parts by weight of processing oil TDAE, 4 parts by weight of diphenylmethane diisocyanate, 5 parts by weight of zinc oxide, 1.8 parts by weight of stearic acid, 2 parts by weight of antioxidant RD, 5 parts by weight of phenylenediamine antioxidant, 6 parts by weight of sulfur, and 0.6 parts by weight of vulcanization accelerator NS are mixed at 60 rpm and 155°C for 320s, discharged, and left at room temperature for 8h, and then vulcanized at 165°C for 30min using a flat vulcanizer; the remaining steps are the same as in Example 2.
[0049] Effect example
[0050] The following table shows the performance analysis results of the tire rubber materials using Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.
[0051]
[0052] From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention uses 2,2'-[[2-(allyloxy)-1,3-phenylene]bis(methylene)]bis(ethylene oxide), ethylene(chloromethyl)dimethoxysilane, and high specific surface area porous silica to modify the polyetheramine and the resin type, so that it has both anti-slip and puncture resistance properties, which is beneficial to improving the performance of the tire rubber. On this basis, natural rubber and oil-extended styrene-butadiene rubber are used as raw materials, and are mixed with epoxy resin and isocyanate respectively to obtain rubber A and rubber B, and then rubber A and rubber B are mixed together to obtain the final The rubber can improve the strength of the formula through the combination of rubber and resin, making the tire more grippy, and the epoxy resin and isocyanate can cross-link with the modified resin to introduce a new cross-linking network, thereby improving the modulus and strength of the prepared tire rubber. After the tire is punctured, the surface of the punctured object can be covered to prevent the rapid leakage of gas inside the tire. The mixing process of the present invention can reduce the blending time between different polymers and reduce the blending temperature, thereby reducing the compatibility between multiphase polymers, thereby better maintaining the glass transition temperature characteristics of the polymer itself and maintaining the grip ability.
[0053] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A rubber compound for improving tire grip performance by changing the resin type, characterized in that: The rubber material is prepared by the following method: (1) Mix polyetheramine, 2,2'-[[2-(allyloxy)-1,3-phenylene]bis(methylene)]bis(ethylene oxide) and catalyst in a molar ratio of 1.5-3:1:0.003, react at 80-135°C for 12-72h under nitrogen protection, and then evacuate to -0.08-0.095MPa for 30-40min to obtain a pretreated resin; (2) Pretreated resin, ethylene (chloromethyl) dimethoxysilane, sodium ethoxide, and sodium iodide were mixed in a mass ratio of 100:1-3:0.1-0.4:0.1-0.4, reacted at 55-60°C for 12 hours, and then extracted with water. The organic phase was treated at a vacuum degree of -0.08--0.095 MPa and 60°C for 30-40 minutes, and high specific surface area porous silica with a mass of 0.5-1.0 times that of the pretreated resin was added, and stirred at 500-800 rpm for 20 minutes to obtain a modified resin; the high specific surface area porous silica was prepared by mixing water glass solution and slaked lime to generate calcium silicate particles, and then acid leaching, with a specific surface area of 704-870 m 2 / g; (3) kneading 8-16 parts by weight of modified resin, 30-50 parts by weight of natural rubber, 40-60 parts by weight of oil-extended styrene-butadiene rubber, 30-40 parts by weight of white carbon black, 7-10 parts by weight of silane coupling agent, 1-3 parts by weight of epoxy resin and 4-7 parts of processing oil TDAE at 150° C. for 4 min to obtain rubber A; (4) 8-16 parts by weight of modified resin, 30-50 parts by weight of natural rubber, 10-15 parts by weight of carbon black N234, 1-3 parts by weight of silane coupling agent, and 3-6 parts by weight of isocyanate were kneaded at 160° C. for 4 minutes to obtain rubber B; (5) Take 100 parts by weight of rubber A and 100 parts by weight of rubber B and mix them at 60 rpm for 5 to 20 seconds. Add 5 to 10 parts by weight of zinc oxide, 1.5 to 2.0 parts by weight of stearic acid, 1 to 3 parts by weight of antioxidant RD, and 3 to 12 parts by weight of antioxidant and mix for 20 seconds. Then add 5 to 8 parts by weight of sulfur and 0.5 to 1 part by weight of vulcanization accelerator NS. After mixing for 3 minutes, drain the rubber at 125°C, leave it at room temperature for 8 hours, and then vulcanize it at 165°C for 30 minutes using a flat vulcanizer.
2. The rubber material for improving tire grip performance by changing resin type according to claim 1, characterized in that: The polyetheramine in step (1) is polyetheramine D2000 or polyetheramine M2070.
3. The rubber material for improving tire grip performance by changing resin type according to claim 1, characterized in that: The catalyst in step (1) is prepared by mixing boron trifluoride etherate and zinc chloride in a mass ratio of 2:
1.
4. The rubber material for improving tire grip performance by changing resin type according to claim 1, characterized in that: The natural rubber in steps (3) and (4) is SMR20.
5. The rubber material for improving tire grip performance by changing resin type according to claim 1, characterized in that: The oil-extended styrene-butadiene rubber in step (3) is SBR1712.
6. The rubber material for improving tire grip performance by changing resin type according to claim 1, characterized in that: The silane coupling agent in steps (3) and (4) is n-octyltriethoxysilane.
7. The rubber compound for improving tire grip performance by changing resin type according to claim 1, characterized in that: The epoxy resin in step (3) is one or a mixture of glycidyl ester epoxy resin, glycidyl ether epoxy resin, and glycidyl amine epoxy resin.
8. The rubber material for improving tire grip performance by changing resin type according to claim 1, characterized in that: The isocyanate in step (4) is isophorone diisocyanate or diphenylmethane diisocyanate.
9. The rubber compound for improving tire grip performance by changing resin type according to claim 1, characterized in that: The antioxidant in step (5) is a phenylenediamine antioxidant.
Citation Information
Patent Citations
Method for producing silica-containing dispersions containing polyetherols or polyetheramines
CN102387991A
Low-heat-generation, tear-resistant rubber composition for engineering tire and preparation method therefor
WO2022100629A1